Enhancing Language Skills in Individuals with Intellectual Disabilities Through Mobile Applications - Prof. Hanadi Hussain Alqahtani; Prof. Mefleh Qublan B Al-Juda (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
Mobile applications have become essential tools in supporting the development of language skills for individuals with intellectual disabilities. This review explores the effectiveness of mobile apps specifically created for this group, focusing on their impact, functionality, and associated challenges. The findings reveal several important points: first, both research evidence and user reviews consistently highlight the positive effects of apps like "Language Learner Pro," "Talk2Learn," "Language Builder Plus," and "Speech and Language Companion" in improving vocabulary, grammar understanding, and social communication. Additionally, advancements in app design, such as speech recognition and personalized learning pathways, have greatly enhanced user engagement and customized learning experiences. However, issues such as device compatibility, accessibility obstacles, and financial costs remain significant barriers. Ethical concerns, particularly around data privacy and user consent, also require careful consideration in app development and usage. Looking ahead, the paper suggests future innovation should prioritize user-centered design, foster collaborative efforts, and encourage ongoing research to enhance educational outcomes. By addressing these challenges thoughtfully and embracing technological advancements, stakeholders can unlock the full potential of mobile apps to support language learning for individuals with intellectual disabilities.